Posterior Urethral Valves: The Spectrum of Radiological and Clinical Presentations - Collet, Victoria; Chiodini, Benedetta; Hennaut, Elise; Khelif, Karim; Luyckx, Stephane; Ismaili, Khalid (Belgian Journal of Paediatrics, 2025)
Objectives: Posterior urethral valves (PUV) are the most common cause of congenital lower urinary tract obstruction (LUTO) and end-stage renal disease (ESRD) in boys. They are suspected on prenatal ultrasound (US) revealing bilateral ureterohydronephrosis, megabladder and posterior urethral dilatation. PUV presents with variable clinical severity and radiological images. This study aims to review the PUV cases in our center, describe the imaging aspects, assess renal and bladder outcome of prenatally and postnatally diagnosed. Methods: We reviewed the medical records of all boys who underwent PUV ablation in HUDERF between 2006 and 2021. We recorded prenatal and peri-operative US, age and symptoms at diagnosis, cystourethrogram, outcome of renal and bladder function. Prenatally and postnatally diagnosed patients were compared. Results: We included 50 boys treated for PUV with available antenatal data. Thirty-one patients (62%) presented an abnormal fetal screening: 90% showed the classic PUV antenatal presentation: bilateral ureterohydronephrosis and megabladder. Three patients had an uncommon fetal presentation with unilateral (uretero)hydronephrosis. Nineteen (38%) were postnatally diagnosed, median age of 9 months. The most common postnatal clinical presentations were urinary tract infections (84%) and voiding disorders (11%). 34% of patients, with similar proportion between antenatally and postnatally diagnosed, reached CKD grade 2-4; 6% progressed to ESRD, all antenatally diagnosed. Conclusions: This study shows an improvement in fetal screening for PUV. Although most of those fetuses showed the classic antenatal presentation, 10% presented an unilateral dilatation with no sign of LUTO. Children diagnosed antenatally showed the worst prognosis in terms of renal and bladder function.